ISLÂM DAN PEREKONOMIAN ISLÂM DALAM PEMERINTAHAN MODERN - Nashar - (Al-Ihkam: Jurnal Hukum dan Pranata Sosial)
the basic 0f Islamic ekonomy, it is actually different with the basic of Modern Economic System. Because of the view of islam for ekonomy have the characteristic what may be in Modern Economic System. Islam has the guidence based the Al-Qur’ an and Hadist and the guidence has the interpretation. The system difference between Islam versus Modern System bears a conclusion : Islamic Ekonomy continuesly and by the all aspects compleyely concerning humanism. Islam has a economic system having the principle of responsibility towards a social community, social living have ability and population economic stimulation. So for the last wise is done by government will always relate with all element of society. There are some economic system is not ruled yet in the sources of Islamic law, as the poroblems of ekonomic system; BUDGET, so it needs to be new Ijtihad, therefore, that system always bases on the social service and in line with the guidence of islamic law.